1247 Bayley Infant Neurodevelopmental Screener (BINS) in Brazilian Preterm Children Under Risk Conditions. (October 2012) - Guedes, DZ; Primi, R; Marteleto, MRF; Kopelman, BI
Abstract : Preterms are always at risk for neurological abnormalities and developmental delays. Underdevelopment country children face multiple adversities and are subjected to biological and social risk factors, fighting daily against mortality. This research purpose was investigating Bayley Infant Neurodevelopmental Screening - BINS (Aylward, 1995) psychometric properties and its effectiveness while screening Brazilian children. BINS was administered to 61 children, low-income families, Brazilian unified health system users, in 2 groups: 31 children-12 months (12m) and 30 children-24 months (24m), both sexes, birth weight < 2000g. Neurologists examined them through Amiel-Tison and Denver-DDST-II and psychologists screened them with BINS -12m/24m and Bayley Scales-BSID-II, golden standard instrument. BINS is a low cost fast screening instrument. It takes 10 minutes to be administered. Consists of 11–13 items and assesses cognitive processes, receptive, expressive functions and basic neurological functions/intactness. The items failed, shows the levels of risk: low, moderate or high risk for neurological impairment or developmental delay. Sociodemographic aspects and birth risk conditions presented homogeneous characteristics. From 61 infants screened, 54 were eligible for the Early Intervention Program in Brazil: 30 infants(12m) and 24 infants(24m). Children were referred to specialists (developmental pediatricians, neurologists, optometrists, speech pathologists, psychologists). BINS reliability indexes were over requested standards. Validity evidences based on external variables were positive moderated and BINS(24 m)/BSID-II (mental) presented high correlation. Validity evidences based on content were attested by expertise. High sensitivity was found. BINS is a satisfactory screening tool and presents adequate psychometric properties. It's also able to screen children under biological and social risk conditions.